EFFECT OF KETOGENIC DIET ON COGNITIVE AND MOTOR FUNCTIONS IN CHILDREN WITH DRUG-RESISTANT EPILEPSY - E. G. Lukyanova; S. O. Ayvazyan; K. V. Osipova; T. N. Sorvacheva; E. A. Pyreva (Эпилепсия и пароксизмальные состояния)
Objective. We describe our experience of using the ketogenic diet (KD) for the treatment of drug-resistant epilepsy. Refractory epilepsy causing irreparable damage to the health of patients giving an epileptic encephalopathy with regression of cognitive and motor functions especially in childhood.Materials and methods. We observed 95 patients, the children from 1 year to 14 years old with refractory epilepsy with frequent seizures.Results. For 20% of children with drug-resistant epilepsy using KD with or without anticonvulsant therapy resulted to treating and prevention of all types of seizures. The improvement of the quality of life for them we estimated by Hague and QLS scales. Using the KD we have achieved the reliable positive changes in the psychomotor development of patients tested by Griffits 1, Griffits 2, and GMFM scales.Conclusions. KD is an effective treatment for refractory epilepsy. The overall efficiency (seizure reducing more than 50%) was observed in 48 patients, representing 48% of the total. The use of the KD will improve the quality of life of patients.